The administration of Lactobacillus plantarum directly to food: An effective way to improve the survival and growth of juvenile lined seahorses (Hippocampus erectus). (4th June 2019) - Lin, Tingting; Liu, Xin; Zhang, Dong; Cai, Yishan; Yan, Zhenzhen
Abstract: Previously, we found Lactobacillus plantarum had probiotic effects on lined seahorse ( Hippocampus erectus ) juveniles by the addition Lactobacillus directly into rearing seawater containing juveniles and their food (i.e. copepods). However, how the juveniles consumed Lactobacillus, directly from water or from copepods in whose guts Lactobacillus may have accumulated by ingestion, is still unclear. To clarify this, three experiments were successively carried out in this study. In the first experiment, the manner by which juveniles consumed Lactobacillus, namely, directly from food, was discovered via a 2 × 2 factorial design with two factors of water and food, and two levels with and without L. plantarum . In the second experiment, a 5 × 4 factorial design with five levels of L. plantarum doses (D: 5, 10, 20, 40 and 80 × 10 8 cfu/L) and four levels of enrichment time (T: 0.5, 1.0, 1.5 and 2.0 hr) was conducted to analyse lactic acid bacteria (LAB) contents in the enriched copepods under different treatments. In the third experiment, six kinds of Lactobacillus ‐enriched copepods chosen from the second experiment that carried significantly different LAB contents were fed to juveniles, and it was found that the copepods containing LAB greater than 5 log10 colonies/g had the most improved effects for survival and growth. In conclusion, the effective manner of L. plantarum administration in seahorses is by the addition to their food. Additionally, D40 * T1.0, whose LAB content was more than 5 log10 colonies/g, is generally the most economic copepod treatment for improving survival and growth in H. erectus rearing.